Experimental study on application of high temperature reactor excess heat in the process of coal and biomass co-gasification to hydrogen-rich gas. (1st May 2015) - Howaniec, Natalia; Smoliński, Adam; Cempa-Balewicz, Magdalena
Abstract: The paper presents the results of the experimental study on the simulated application of HTR (High Temperature Reactor) excess heat in the process of allothermal co-gasification of coal and biomass. The laboratory scale installation with a fixed bed gasifier and auxiliary gasification agents pre-heating system, simulating the utilization of the HTR excess heat, were applied in the study. Steam and oxygen were the gasification media employed, and the process was focused on hydrogen-rich gas production. The results of the co-gasification of fuel blends of various biomass content at 800 °C and in various system configurations proved that the application of the simulated HTR excess heat in pre-heating of the gasification agents leads to the increase in the gaseous product yield. Furthermore, the HCA (Hierarchical Clustering Analysis) employed in the experimental data analysis revealed that the gasification of fuel blends of 20 and 40%w/w of biomass content results in higher volumes of the total gas, hydrogen, carbon monoxide and carbon dioxide than gasification of fuel blends of higher biomass content. Highlights: Simulated utilization of HTR excess heat in co-gasification of coal and biomass. Assessment of three system configurations in terms of hydrogen production. Application of the HCA in the experimental data set analysis. Variation in gas components volume and content with fuel blend composition.